2004
DOI: 10.1002/adsc.200404220
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Carbometalation/Cross‐Coupling Sequence across Alkynyl(2‐pyridyl)silanes Leading to a Diversity‐Oriented Synthesis of Tamoxifen‐Type Tetrasubstituted Olefins

Abstract: A general synthetic scheme for tamoxifentype tetrasubstituted olefins based on the novel Cucatalyzed carbomagnesation across alkynyl(2-pyridyl)silane has been developed. A wide array of electronically and structurally diverse tetrasubstituted olefins can be prepared in a regiocontrolled, stereocontrolled, and diversity-oriented manner. Noteworthy features are that (i) the three aryl groups, which are believed to be important (essential) for anti-estrogenic activity, can be varied at will because they all stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 79 publications
0
23
0
1
Order By: Relevance
“…Of note, the overall three‐step transformation of m ‐iodotoluene into pivaloxylated arene 16 constitutes a formal ortho ‐oxygenation of m ‐iodotoluene 32. Moreover, borodesilylation of the PyDipSi group in 4r with BCl 3 , followed by the protection of the generated aryldichloroborane with pinacol under basic conditions,7d,33 furnished a synthetically valuable arylboronate 17 34 in an excellent yield. Likewise, a one‐pot sequence involving the borodesilylation of 4r , followed by the oxidation step in the presence of H 2 O 2 /NaOH, led to 4‐methylcatechol ( 18 ) in 89% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the overall three‐step transformation of m ‐iodotoluene into pivaloxylated arene 16 constitutes a formal ortho ‐oxygenation of m ‐iodotoluene 32. Moreover, borodesilylation of the PyDipSi group in 4r with BCl 3 , followed by the protection of the generated aryldichloroborane with pinacol under basic conditions,7d,33 furnished a synthetically valuable arylboronate 17 34 in an excellent yield. Likewise, a one‐pot sequence involving the borodesilylation of 4r , followed by the oxidation step in the presence of H 2 O 2 /NaOH, led to 4‐methylcatechol ( 18 ) in 89% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Kamei et al have reported the synthesis of tamoxifen analogues using alkynyl(2-pyridyl)silanes (459) which were synthesized from the reaction of dimethylsilylchloride (455) with 1-butynylmagnesium chloride (456) in THF to give compound 457 in 51% yield followed by reaction with 2pyridylmagnesium chloride (458) in THF to afford 459 in 61% yield (Scheme 89). [94] Compound 459 was further reacted with Grignard reagent 460 in regio-and stereo-specific manner in the presence of CuI in diethyl ether to give 461. Further investigation in this reaction step led to the conclusion that the use of 3-pyridyl-, 4-pyridyl-, and phenyl(1-butynyl)silanes did not lead to any reaction which implicated the strong directing effect of 2-pyridyl group.…”
Section: Addition Reaction To Alkynesmentioning
confidence: 99%
“…Itami ist seit 1998 Assistant Professor an der Universität Kyoto, wo er neue Reagentien und Methoden für die organische Synthese entwickelt und deren Mechanismen erforscht. Kürzlich berichtete er über eine Reaktionsfolge aus katalytischer Carbometallierung und Kreuzkupplung zur Synthese vierfach substituierter Olefine 4. Itami studierte an der Universität Kyoto und promovierte dort 1998 unter der Anleitung von Y. Ito über übergangsmetallkatalysierte Cycloadditionen an Vinylallene.…”
Section: Ausgezeichnet…︁unclassified